Study of Resettlement Programmes for Landless Agricultural Labourers - Planning Commission (Planning Commission, 1966)
The PEO studies will be gradually oriented towards the type of intensive case-study as being undertaken during the current year. We thought, therefore, that it would be appropriate to bring together in the form of a booklet all the methodological papers including objective, scope, sample, schedules etc. and instructions for the convenience of the investigating officers. This booklet is the result of the joint efforts of all the officers of the PEO, specially of those of the I.E. Division. The time and labour spent on the preparation of such a booklet will be fully justified if the field investigations can be completed with greater clarity, perfection and in time.
Design Schedules Etc. and Instructions Programme Evaluation Organisation Planning Commission